Use of Biomedical Engineering for Rehabilitation of Patients with Disability Caused by Guillain-Barré Syndrome: a Systematic Review. - Torres-Reyes, Andrés Burjand; Reyes-Hernández, Ivette; Domínguez-Ramírez, Omar Arturo; Tellez-Lopez, Ana María (Revista Mexicana de Ingeniería Biomédica)
This systematic review aims to assess the extent to which biomedical engineering has been applied in the rehabilitation of patients suffering from Guillain-Barré Syndrome (GBS), given the scarcity of information on this topic. We conducted a thorough analysis of research articles, conference abstracts, and case reports published between 2000 and 2023, specifically from ScienceDirect, PubMed, IEEE Xplore, Springer, and Dimensions. 19 articles were extensively discussed, complemented by an additional 40 information sources providing supplementary information. Each paper underwent a meticulous review process by the four authors, where each separately examined the title and abstract of the papers and subsequently provided a thorough examination of the full text; when conflicts arose, a clear consensus was reached through discussion. The analysis of the articles revealed a notable improvement in upper and lower limb function of GBS patients that was facilitated by both custom-made and commercial devices. Likewise, a small handful of other devices have been used (e.g., to improve urinary retention issues). There is a clear opportunity for new research, innovation and applications.